Optimization of seed production techniques in a single cross maize hybrid - K.S. VINUTHA; S. RAJENDRA PRASAD; RAME GOWDA; P. RAVISHANKAR; S.P. JEEVAN KUMAR; J. SHANTHALA (Seed Research, 2026)
Synchronization of parental lines is a basic need for hybrid seed production technology to improve seed setting. To optimize the seed production techniques staggered sowing, planting ratios and subtending cob leaf clipping were performed in single cross maize hybrid Hema with NAI-137, female and MAI-105, male parent during kharif 2011. The results implicates that the synchronization of flowering was attained by sowing male parent (MAI-105) three days earlier to female parent (NAI-137) with a planting ratio of 6:2 resulted 50% female silking in 56.83 days with concomitant higher seed yield (130.86 g/plant). However, clipping had no effect on seed yield of single cross maize hybrid Hema.